Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008 IEEE International Electron Devices Meeting 2008
DOI: 10.1109/iedm.2008.4796604
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic correlation between mobility reduction and V<inf>t</inf> shift due to interface dipole modulation in HfSiON/SiO<inf>2</inf> stack by La or Al addition

Abstract: Intrinsic correlation between mobility reduction by remote Coulomb scattering (RCS) and threshold voltage shift (ΔV t ), both of which are induced by interface dipole modulation at high-k/SiO 2 interface, is investigated. Three types of dipole modulation are examined; Al addition, La addition, and changing quality of interfacial SiO 2 layer. Extrinsic scattering components due to increases of interface state and surface roughness are extracted and separated. It is found that RCS due to interface dipole modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…Mobilityfluctuation noise is closely connected to mobility degradation phenomenon through identical scattering mechanism [11]. Tatsumura et al [12] and C. Y. Kang et al [4] have reported that in La-doped HfSiON/metal gate nMOSFETs, La-doping caused mobility degradation at low field conditions and it was attributed to remote Coulomb scattering by La-induced dipole at high-k/IL interface. Therefore, the additional mobilityfluctuation noise of submicron La-doped devices for V gt ≤ 0.1 V may be attributed to remote Coulomb scattering by the Lainduced dipole.…”
Section: Resultsmentioning
confidence: 98%
“…Mobilityfluctuation noise is closely connected to mobility degradation phenomenon through identical scattering mechanism [11]. Tatsumura et al [12] and C. Y. Kang et al [4] have reported that in La-doped HfSiON/metal gate nMOSFETs, La-doping caused mobility degradation at low field conditions and it was attributed to remote Coulomb scattering by La-induced dipole at high-k/IL interface. Therefore, the additional mobilityfluctuation noise of submicron La-doped devices for V gt ≤ 0.1 V may be attributed to remote Coulomb scattering by the Lainduced dipole.…”
Section: Resultsmentioning
confidence: 98%
“…However, this step also requires a balance between these benefi cial mechanisms and the diffusion of metal from the capping layers to the dielectrics/semiconductor interface, which would cause deleterious V t shifts and mobility degradation. 32 The rest of the gate-fi rst fl ow follows the conventional CMOS fl ow.…”
Section: Process Integration Of Metal Gate Electrodesmentioning
confidence: 99%
“…Next, the NMOS capping layer (typically La 2 O 3 ) is deposited and similarly patterned and wet-etched from the PMOS regions. 32 The metal nitride gate electrode and polysilicon top electrode are deposited, and the entire gate stack must be patterned to defi ne the active gates. The next critical step occurs during the junction activation, which exceeds temperatures of 1000°C.…”
Section: Process Integration Of Metal Gate Electrodesmentioning
confidence: 99%
“…10) generations, while a number of researchers have investigated the ability to set near band edge work functions for gate-first using selective capping layers such as La 2 O 3 for N-metaloxide-semiconductor (NMOS) 11 and Al 2 O 3 for P-metal-oxidesemiconductor (PMOS). 12 However, there are a number of issues to using this technique particularly for PMOS where an ideal capping layer that does not cause equivalent oxide thickness (EOT) and mobility degradation has been elusive. 12 Conversely, gate-last technologies have also been demonstrated for the 45 nm (Ref.…”
mentioning
confidence: 99%
“…12 However, there are a number of issues to using this technique particularly for PMOS where an ideal capping layer that does not cause equivalent oxide thickness (EOT) and mobility degradation has been elusive. 12 Conversely, gate-last technologies have also been demonstrated for the 45 nm (Ref. 13) and 32 nm (Refs.…”
mentioning
confidence: 99%